2021
DOI: 10.1039/d0sm00150c
|View full text |Cite
|
Sign up to set email alerts
|

Reversible membrane deformations by straight DNA origami filaments

Abstract: Reversible MgCl2-induced blunt-end polymerization of membrane-bound straight DNA origami monomers into filaments leads to protruding deformations on freestanding lipid membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 90 publications
(116 reference statements)
0
47
0
Order By: Relevance
“…The high‐density filaments could trigger the occurrence of spike‐like membrane protrusions on the GUV, which could be reversibly controlled by adjusting the assembly and depolymerization of filaments. [ 138 ] These results indicated that DNA nanostructures could mimic membrane proteins lacking inherent curvature to deform the membrane through the crowding mechanism.…”
Section: Mimic Membrane Deformation and Heterogeneous Membrane Fusionmentioning
confidence: 99%
“…The high‐density filaments could trigger the occurrence of spike‐like membrane protrusions on the GUV, which could be reversibly controlled by adjusting the assembly and depolymerization of filaments. [ 138 ] These results indicated that DNA nanostructures could mimic membrane proteins lacking inherent curvature to deform the membrane through the crowding mechanism.…”
Section: Mimic Membrane Deformation and Heterogeneous Membrane Fusionmentioning
confidence: 99%
“…Large flat sections appeared on the GUV with kinks at the phase boundaries between the polymerized flat DNA sheets. In addition to the morphological change, we observe a suppression of membrane fluctuations (Supplementary Figure S13, Video S5), indicating a mechanical stabilization of the compartment [35,43] by the DNA-based cytoskeleton mimic. Both the morphological and the mechanical alterations are reversible: Addition of a base led to pH decrease and hence to the detachment of the DNA origami from the GUV membrane.…”
Section: Ph-induced Morphology Changementioning
confidence: 88%
“…Instead of relying on purified proteins, an increasingly popular approach is to construct such pH-dependent machineries de novo from molecular building blocks. DNA nanotechnology, in particular, has been employed to build a variety of functional components for synthetic cells, [17,30,31] including membrane-sculpting [32][33][34][35] and pH-responsive components such as filaments [36] or rotors. [37,38] However, pH-responsive actuation is challenging after encapsulation into a compartment.…”
Section: Ph-sensitive Attachment Of Dna To the Compartment Peripherymentioning
confidence: 99%
“…In a more recent study, the same group developed straight origami DNA filaments that could reversibly deform GUVs. 180 DNA clathrin-mimics were also shown to cause deformations similar to clathrin-coated pits 181 and DNA nanosprings to cause GUV tubulation. 182 It has also been shown that DNA nanopores (discussed in a later section) cluster and remodel membranes into protrusions and can facilitate the formation of ultrathin lipid tubes.…”
Section: Applications At the Interface Of Dna Nanostructures And Lipimentioning
confidence: 99%